Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Kebijakan Dividen terhadap Nilai Perusahaan - Yunitasari, Yunitasari; Nurdhiana, Nurdhiana (STIE Widya Manggala, 2013)
Company’s value is the prosperity of the company’s owner showed by the increasing value of the company which is reflected in its share price. Considering many factors that affect the value of the company, the research was conducted to examine the effect of investment decisions, funding decisions and dividend payout ratio in manufacturing companies period 2009-2011. The populations were 326 manufacturing companies, while 25 companies manufacturing were taken as samples. Non probabitlitysampling technique was purposive sampling method. The analytical tool used in this study was multiple linear regression. The results showed the investment decisions and financing decisions had significant positive effect on company’s value while the dividend payout ratio had no effect on company’s value. Investment decisions, funding decisions and dividend payout ratio simultaneously affected 23.00 % of the value of the company while the remaining 77.00 % were explained by causes outside the model.